The Artistic-aesthetic and Educational Importance of Comedy in the Formed Studies in Uzbek Children's Literature in the Independence Period - Jurayeva, Gulnoza (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the issues of children's literature in the period of independence. Lyrical works are analyzed in terms of themes and artistic color. Samples of poems by poets created during the independence period are consistently drawn into artistic analysis. Its formal and logical development is studied and recognized. Where appropriate, the works of contemporary artists are compared to the poetry of master poets. It is acknowledged that humorous poems not only enrich the spiritual world of children, but also have a great educational value. Written with the participation of the alphabet, letters and punctuation, this category of poems is taught to help children think seriously about literacy and expand their worldview. Humorous poems about children focus more on the spiritual and moral issues associated with renewal in social development than on the minor flaws in the behavior of children. These features become an aesthetic principle, revealing the educational significance of the period of independence in Uzbek children's literature. The article examines the rise of Uzbek children's poetry since independence.